2009
DOI: 10.1142/s1793524509000728
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Cumulative Effect of Ecological Factors in the Habitat on the Spread of Tuberculosis

Abstract: In this paper, the cumulative effect of ecological factors in the habitat on the spread of tuberculosis (TB) in human population is modeled and analyzed. The total human population is divided into two classes, susceptibles and infectives. It is assumed that TB is not only spread by direct contacts with infectives in the population but also indirectly by bacteria which are emitted by infectives in the habitat. It is assumed further that bacteria survive due to conducive ecological factors such as flower pots, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Based on this in [4], authors formulated a model where variable human and bacteria populations are taken into account and it is concluded that due to bacteria in the environment, equilibrium level of the infective population increases. The global properties of a very general tuberculosis model with two differential infectivity is discussed in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this in [4], authors formulated a model where variable human and bacteria populations are taken into account and it is concluded that due to bacteria in the environment, equilibrium level of the infective population increases. The global properties of a very general tuberculosis model with two differential infectivity is discussed in [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we present a model for the disease situation in India, one of the countries in which the disease is endemic. This work is an extension of previous results, [3,15,18] and in particular of the work in progress [19], in that we account for the diagnostic system to be partioned into the public and private sectors, contrary to what was assumed in the earlier works.…”
mentioning
confidence: 87%
“…The spread of tuberculosis model [50] is the system of four differential equations with respect to time along with four variables that can be denoted together as a quaternion number instead of four real numbers. This model needs the intelligent behavior and automated analysis of bacterial effect to reach equilibrium from different initial conditions.…”
Section: A Function Approximation Of Model For Spread Of Tuberculosismentioning
confidence: 99%